The single-nucleotide polymorphism (SNP) of tumor necrosis factor α −308G/A gene is associated with early-onset primary knee osteoarthritis in an Egyptian female population - Abdel Galil, Sahar M.; Ezzeldin, Nillie; Fawzy, Faten; El-Boshy, Mohamed (Clinical rheumatology, 2017)
The objective of the present study is to investigate if there is a potential association between the single-nucleotide polymorphisms (SNPs) of the tumor necrosis factor alpha gene (TNF-α −308G/A, rs1800629) and the susceptibility to and severity of early-onset knee osteoarthritis in the Egyptian female population. Genotype distributions and allelic frequencies of TNF-α −308G/A polymorphism were investigated in 210 knee osteoarthritis (OA) patients and 210 age-, sex-, and ethnicity-matched healthy controls (HC). Polymerase chain reaction-restricted fragment length polymorphism (PCR-RFLP) amplifications were implemented to determine TNF-α −308G/A SNP. Serum and synovial fluid levels of TNF-α, besides ESR and CRP, as laboratory markers for inflammation, were estimated for all patients and HC. Plain X-ray as well as MRI knee was done for grading of OA. Disease severity was estimated by Western Ontario and McMaster University Osteoarthritis scores. Percentages of TNF-α-G308A genotypes GG, AG, and AA were 85.7, 11.9, and 2.4% in OA patients and 54.7, 39.1, and 6.2% in controls, respectively. The frequencies of the GG genotype and G allele were significantly higher in subjects with knee OA than in HC ( P = 0.04 and P < 0.001, respectively). Logistic regression analysis showed that the GG genotype and G allele are independently associated with increased risk for knee OA (odds ratio = 3.13, 95% confidence interval = 1.04–9.39, P = 0.04 for GG genotype, and odds ratio = 3.81, 95% confidence interval = 2.52–5.76, P = 0.001 for G allele). There is a close relationship between TNF-α-G308A polymorphism and individual susceptibility to and severity of early-onset knee OA in the Egyptian females.